SEJARAH PERKEMBANGAN KURIKULUM DI INDONESIA SEJAK AWAL KEMERDEKAAN HINGGA SAAT INI - Insani, Farah Dina (AS-SALAM, 2019)
This article aims to describe the history of the development of the Indonesian education curriculum from 1945 to the present. Curriculum improvements are carried out at least once every ten years. Because within the past ten years, it is very possible that there will be changes in various fields such as information, communication technology and science. The method used in this research is the documentation method as used in data collection techniques in library research (library research). The object of study in this article is focused on tracing the history of curriculum development in Indonesia from the beginning of independence to the present. The results of this study indicate that the curriculum in Indonesia has been developed twelve times, namely in 1947, 1952, 1964, 1968, 1973, 1975, 1984, 1994, 1999, 2004, 2006 and 2013. The positive contribution expected from this article is that the public is educated on the history of curriculum development in Indonesia and can be used as a basis for future curriculum development to create quality students who are ready to compete internationally.